PENGARUH PENGGUNAAN KECERDASAN INTELEKTUAL (IQ), EMOSIONAL (EQ) DAN SPIRITUAL (SQ) TERHADAP KINERJA PEGAWAI INSPEKTORAT (STUDI PADA KANTOR INSPEKTORAT PROVINSI KALIMANTAN SELATAN) - Akhid Yulianto; Hari Nugroho Akimas (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2022)
This study aims to determine: (1) The influence of intellectual intelligence (IQ) on the performance of the Inspectorate of South Kalimantan Province, (2) the influence of Emotional Intelligence (EQ) on the performance of the employees of the Inspectorate of South Kalimantan Province, and (3) the influence of spiritual intelligence (SQ). on the performance of the employees of the Inspectorate of South Kalimantan Province. The population in this study were all employees of the South Kalimantan Inspectorate Office, amounting to 56 people. This amount is used as a sample at the same time. The data collection method used in this study used a questionnaire. The data analysis technique used is Structural Equation Modeling- Partial Least Square (SEM-PLS). Based on the results of the analysis in this study, it shows that intellectual intelligence (IQ) has no significant effect on the performance of the employees of the Inspectorate of South Kalimantan Province. Emotional Intelligence (EQ) has a significant effect on the performance of the Inspectorate of South Kalimantan Province employees. Spiritual Intelligence (SQ) has a significant effect on the performance of the company's employees of the Inspectorate of South Kalimantan Province